2012
DOI: 10.1111/j.1525-1470.2012.01797.x
|View full text |Cite
|
Sign up to set email alerts
|

Reporting, Representation, and Subgroup Analysis of Race and Ethnicity in Published Clinical Trials of Atopic Dermatitis in the United States Between 2000 and 2009

Abstract: To review the literature on atopic dermatitis (AD) clinical trials published in the United States between 2000 and 2009 to examine the representation of racial and ethnic minorities in those trials and determine the extent to which investigators reported on demographic variables and performed a subanalysis. A PubMed search was performed including all clinical trials for management of AD published between 2000 and 2009. Three reviewers analyzed articles matching the search criteria. Data recorded included incor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
49
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(52 citation statements)
references
References 16 publications
0
49
0
Order By: Relevance
“…In fact, a study has found the underreporting of patient’s skin type in clinical trials, with only 59.5% of the clinical trials published in the United States between 2000 and 2009 reporting the patient’s race or ethnicity (Hirano et al, 2012). Another systematic review showed that there is a dearth of studies demonstrating efficacy of systemic AD therapy in different racial and ethnic patient subsets in the United States (Bhattacharya and Silverberg, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…In fact, a study has found the underreporting of patient’s skin type in clinical trials, with only 59.5% of the clinical trials published in the United States between 2000 and 2009 reporting the patient’s race or ethnicity (Hirano et al, 2012). Another systematic review showed that there is a dearth of studies demonstrating efficacy of systemic AD therapy in different racial and ethnic patient subsets in the United States (Bhattacharya and Silverberg, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…9 The US Food and Drug Administration (FDA) currently requires that all investigational new drug and new drug applications studies include demographic information prior to approval. 10 Additionally, National Institutes of Health (NIH)-funded clinical research studies must include women and minorities. 11 Despite a call to action to achieve diversity in research, that we know of there has been no systematic evaluation of clinical and research diversity among dermatology research subjects to date.…”
mentioning
confidence: 99%
“…Previous studies examined European and American (Caucasian) subjects, while the subjects in the present study were Asian. Allergic diseases have different epidemiological 12,16,18,24 and clinical 3,15,16,20 manifestations, and may involve different genetic and epigenetic mechanisms 11,29,32 depending on ethnicity, which may in turn be associated with variable glioma risk Eosinophil counts were found to be higher in cases than controls, while the values were within normal ranges. Moreover, blood eosinophil counts and immunoglobulin E levels are dynamic.…”
Section: Discussionmentioning
confidence: 99%
“…35 Moreover, ethnic differences in the prevalence and manifestation of allergies and related diseases have been reported. 7,15,16 Earlier studies examining the association between allergies and gliomas mostly focused on respiratory and food allergies Increased rate of positive penicillin skin tests among patients with glioma: insights into the association between allergies and glioma risk in European and American Caucasian patients; as such, information on other types of allergies in other patient populations is needed. Unlike allergies such as asthma that can be provoked by a variety of factors, allergic reactions to drugs have a well-defined mechanism, which is useful for evaluating disease associations.…”
mentioning
confidence: 99%